Development of an Alumni Data Analytics Application to Support Strategic Decision-Making in the Digital Era - พันธ์วงศา, กฤษฎา; นาคมะเริง, ภูมินทร์; ส่วยสิน, พัชรินทร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: (1) develop an application for collecting and managing alumni data for the Faculty of Information Technology and Digital Innovation (ITDI) in mobile and website formats; (2) develop a Real-time Dashboard using data visualization techniques categorized by skills, industry types, and career paths to support executives' digital decision-making; and (3) analyze the distribution patterns of alumni in the labor market to synthesize strategic recommendations for curriculum development. The study employed a Research and Development (R&D) approach by applying the System Development Life Cycle (SDLC) in conjunction with Google Workspace cloud technology. The system was developed using the AppSheet platform connected to a Google Sheets database, and the results were presented through a Real-time Dashboard. The developed system consists of three main modules: the main menu, the data input module, and the information presentation module. It can record data accurately and automatically update statistical charts when new data is entered (Real-time Synchronization).            The results of the system quality evaluation by experts (n=3) and the user satisfaction evaluation by alumni (n=15), using an assessment tool with a reliability coefficient (Cronbach's Alpha) of 0.85, revealed that the overall mean scores for both groups were at a moderate level (x̄= 3.27, S.D. = 0.33). The aspect of reliability and stability received the highest mean score among the users (x̄= 3.38, S.D. = 0.31), while the transparency of personal data usage received a high-level score from the experts (x̄= 3.60, S.D. = 0.51).            The research findings indicate that the system has the potential to support digital decision-making. However, it requires further development in terms of the user interface and Responsive Design, as well as in-depth analytical functions and alumni engagement mechanisms, to enhance the system's strategic value in the long term.